All you can drink: should we worry about quality? - Flores Curiel, Daniel (Springer, 2009)
“All you can drink” specials are forbidden by law in several places. Authorities claim that establishments tend to offer low quality drinks when they use this type of promotion. In this paper, I elaborate a model to determine whether a monopolist produces higher or lower quality goods when using buffet pricing (all you can drink) instead of a two-part tariff. I find that the more profitable strategy is usually associated with a higher quality good than the less profitable strategy. However, under certain conditions buffet pricing is more profitable and leads to lower quality goods than the alternative.